PERENCANAAN STRUKTUR ATAS (UPPER STRUCTURE) JEMBATAN BILAL - Mei Brilian Harefa; Alif Saum Rizalitaher; Aroli Harefa (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2023)
Bridges are one of the important infrastructure in people's lives, because apart from being a link to facilitate transportation between two or more areas separated by rivers and valleys, the existence of bridges can indirectly increase economic growth in an area. Structurally the bridge is separated into an upper building and a lower building. According to its function, the building under the bridge supports and forwards the load from the bridge top building to a strong and stable / solid soil layer. The building under the bridge consists of an abutment and a foundation, where the abutment can also function as a bridge foundation. The upper structure on a bridge includes, among others, vehicle floors (Deck), bridge girders (Girder), bridge stiffeners, laying bridges (Bearing), and expansion joints. This study focuses on the floor of the vehicle (Deck). This study aimed to calculate the bridge floor slab. With the quality of concrete used is FC'30 Mpa, the quality of steel used Fy = 400 Mpa. While field reinforcement (Positive Bending Rebar) is used D32 – 150 reinforcement, for him reinforcement is used D22 – 150. In fulcrum reinforcement (Negative Flexural Rebar) D32 – 150 reinforcement is used and reinforcement for D22 – 150. The total deflection on the bridge floor slab is 0.1668 mm. The shear strength is factored at 379.572 kN.